Research design qualitative, quantitative, and mixed methods approaches - Creswell, John W. (Thousans Oaks, Calif. SAGE Publications, 2009)
Includes bibliographical references and index
Keywords: Social sciences -- Research -- Methodology; Social science -- Statistical methods